Organizational Adaptation in Offshoring: The Relative Performance of Home- and Host-Based Learning Strategies - Asmussen, Christian Geisler; Larsen, Marcus M.; Pedersen, Torben (Organization Science, 2016)
Offshoring offers managers the promise of substantial economic benefits, but also comes with the risk of increased complexity and coordination challenges. We argue that offshoring firms must accumulate architectural knowledge to keep the cost of coordination of the geographically separated activities at bay. Based on a simulation model that examines the performance implications of firms’ learning strategies when offshoring, we show that such knowledge accumulation can be achieved through either a home-based or a host-based learning strategy. Our analysis suggests that the relative performance of these two strategies depends on nontrivial interactions among the costs of communication, the distance to the offshoring location, and the level of noise in the firm’s performance function. In particular, the difficulties of interpreting performance signals in noisy situations suggest that there are benefits of making changes to the configuration after the offshoring implementation (host-based learning). In contrast, when coordination costs and distance dominate, the strategy of gearing the organization for offshoring prior to separating them across country borders prevails (home-based learning). Thus, by formalizing these two learning strategies for acquiring architectural knowledge in offshoring, we show that important contingencies can lead to significant performance trade-offs in the search for new organizational configurations that span international borders.